2010
DOI: 10.1007/s10926-010-9251-7
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to Work if you’re Unwell? Beliefs and Attitudes of Managers and Employees With Musculoskeletal Pain in a Public Sector Setting

Abstract: These issues require careful consideration of the rights and responsibilities of both employees and employers, where strategies for improving communication, trust, and creating an environment conducive to successful return to work need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Nonetheless, statistically significant improvements were observed in all the outcomes shown in Table 2 between the baseline and follow up assessments. Current health status had the strongest association with work-related variables and association was stronger for work performance than for absence, which was similar to findings from a previous study conducted by some of the authors [42,43], and highlights the importance of managing MS pain effectively.…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, statistically significant improvements were observed in all the outcomes shown in Table 2 between the baseline and follow up assessments. Current health status had the strongest association with work-related variables and association was stronger for work performance than for absence, which was similar to findings from a previous study conducted by some of the authors [42,43], and highlights the importance of managing MS pain effectively.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, social relations and social emotions between absentees and family and work-life relations have proven to be important factors in absentees’ rehabilitation [4446]. Knapstad et al [44] found that increased understanding of the impact of social and emotional aspects around sickness absence could be an important source for improved quality of the return to work process.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the barriers to recruitment in this study may reflect wider attitudes towards work, health and the role of research. 91 In the UK, clinical research of this type has achieved high levels of adoption in routine NHS services. Convincing employees and employers of the importance and contribution of high-quality research may be an important first step.…”
Section: Research Recommendationsmentioning
confidence: 99%